Gene expression in the phenotypically plastic Arctic charr (Salvelinus alpinus): A focus on growth and ossification at early stages of development. Issue 1 (26th November 2018) - Beck, Samantha V.; Räsänen, Katja; Ahi, Ehsan P.; Kristjánsson, Bjarni K.; Skúlason, Skúli; Jónsson, Zophonías O.; Leblanc, Camille A.
Abstract : Gene expression during development shapes the phenotypes of individuals. Although embryonic gene expression can have lasting effects on developmental trajectories, few studies consider the role of maternal effects, such as egg size, on gene expression. Using qPCR, we characterize relative expression of 14 growth and/or skeletal promoting genes across embryonic development in Arctic charr ( Salvelinus alpinus ). We test to what extent their relative expression is correlated with egg size and size at early life‐stages within the study population. We predict smaller individuals to have higher expression of growth and skeletal promoting genes, due to less maternal resources (i.e., yolk) and prioritization of energy toward ossification. We found expression levels to vary across developmental stages and only three genes ( Mmp9, Star, and Sgk1 ) correlated with individual size at a given developmental stage. Contrary to our hypothesis, expression of Mmp9 and Star showed a non‐linear relationship with size (at post fertilization and hatching, respectively), whilst Sgk1 was higher in larger embryos at hatching. Interestingly, these genes are also associated with craniofacial divergence of Arctic charr morphs. Our results indicate that early life‐stage variation in gene expression, concomitant to maternal effects, can influence developmental plasticity and potentially the evolution of resource polymorphism in fishes.